Future prospects of alternative agro-based bioenergy use in Finland - constructing scenarios with quantitative and qualitative delphi data - Rikkonen, Pasi; Tapio, Petri (Elsevier Science, 2009)
In this paper, the potential of bioenergy production in agriculture (preferred and probable futures) is scrutinised using the Delphi method. We present a case of northern possibilities to utilise renewable energy sources within agriculture in a form of alternative bioenergy scenarios. Altogether 20 experts participated in the Delphi process which outlines the future of bioenergy production in Finland. The first round of the Delphi study was carried out by semi-structured interviews and the second feedback round by means of a mail questionnaire. Background information of key variables was presented to the panellists who responded with their views on developments between 2004 and 2025. Alternative scenarios were then constructed from these dimensions with cluster analysis in line with the Disaggregative Policy Delphi (DPD) approach. Quantitative statements were complemented with the experts' argumentation. Five scenarios were constructed: 1) Renewable prosperity, 2) Incremental change, 3) Vision of sun, wind and wood, 4) Let's burn it all, and 5) Flood of waterpower. After the Delphi rounds, a dialogue seminar for the agri-technology experts and policy-makers was organised. These results bring to the table an agri-food technology expert community view of the future directions for Finnish agro-bioenergy use.
Keywords: Ma; uusiutuva energia; maatalous; bioenergia; energiantuotanto; agriculture; bioenergy; renewable energy; delphi method; scenario planning; technological foresight